Enzyme-catalyzed allylic oxidation reactions: A mini-review - Wang, Maoyao; Zhou, Xiaojian; Wang, Zhongqiang; Chen, Yongzheng (Frontiers in Chemistry, 2022)
Chiral allylic oxidized products play an increasingly important role in pharmaceutical, agrochemical, and pharmaceutical industries. Biocatalytic C–H oxyfunctionalization to synthesize allylic oxidized products has attracted a lot of interest in recent years, with the ability to simplify synthetic approaches toward complex compounds. As a result, scientists have obtained some new enzymes and mutants by techniques of gene mining and enzyme directed evolution in recent years. This review summarizes the recent developments in biocatalytic selective oxidation of olefins by different kinds of enzymes.